Rearrange to: x^2 + 18x - 25 = 0
Then factorise (I like to do it by completing the square):
(x + 9)^2 -81 -25 = 0
(x + 9)^2 = 106
x + 9 = sqrt(106)
The sol'ns are:
x = -9 + and - sqrt(106)
Answer:
Step-by-step explanation:
P(y) = y³ + 2y² + 2y + 1
P(-1) = (-1)³ + 2*(-1)² + 2*(-1) + 1
= -1 + 2 - 2 + 1
= 0
As, P(-1) = 0, (y + 1) is a factor.
Use synthetic division or remainder theorem.
-1 1 2 2 1
<u> 0 -1 -1 -1 </u>
1 1 1 0
quotient = y² + y + 1
y³ + 2y² + 2y + 1 = ( y + 1) (y² + y + 1)
Area is length times width so it is 3 times 3 since a square sides are all the same